ETIOPATHOLOGICAL STUDY OF MEDODUSHTI W.S.R. TO DYSLIPIDEMIA: A COMPREHENSIVE VIEW - Kumar Ravindra; Akhlak Shehla; Gavali Preeti; Sharma Reetu (International Journal of Applied Ayurved Research, 2022)
Introduction: Ayurveda is a science to achieve hitayu and sukhayu. In Ayurveda, diseases are described along with their causative factors and treatment to achieve and maintain a better health condition. With time, many new diseases like dyslipidemia have appeared because of changes in food habits and life style. In Ayurveda, dyslipidaemia can be studied as medodushti, medoroga, medovaha srotasjanya vikar, sthaulya, ama meda dhatu, rasraktgata snehavriddhi etc. Objectives: Since dyslipidemia is not described specifically in Ayurveda but is only found as symptomatic description, this article attempts to study the disease according to its symptomatology and pathogenesis (samprapti) in Ayurveda. Data Source: Charak Samhita, Sushruta samhita, Ashtanga Hridaya, Modern medical textbooks, journals and online data bases. Review Methods: The classical textbooks and various scientific journals and other databases were reviewed manually. Results: Medodushti can be correlated with dyslipidaemia and is the precursor of medoroga which is a disorder of mainly agni and various causative factors like aaharaj, viharaj, Mansik, beejadosha are held responsible for the condition. Medoroga can be considered as metabolic syndrome as it is group of associated symptoms of impaired fasting glucose, obesity, hypertension and dyslipidaemia. Conclusion: The study intends to study dyslipidaemia as medodushti which symptomatically is silent in disease nature.